Multiclass and multi-residue determination of antibiotics in bovine milk by liquid chromatography–tandem mass spectrometry: Combining efficiency of milk control and simplicity of routine analysis. (August 2016) - Martins, Magda Targa; Barreto, Fabiano; Hoff, Rodrigo Barcellos; Jank, Louise; Arsand, Juliana Bazzan; Motta, Tanara Magalhães Campos; Schapoval, Elfrides Eva Scherman
Abstract: Antibiotics are widely used in veterinary medicine and incorrect practices may lead to drug residues in food, including milk. Fast and simple sample preparation methods have been developed for determination of quinolones, fluoroquinolones, tetracyclines, sulphonamides, trimethoprim and bromexine using liquid chromatography–tandem mass spectrometry. Small volumes of sample (0.5 mL) were extracted using organic solvent followed by centrifugation and evaporation and/or dilution. Validation took into account the maximum residue limits (MRLs). Recoveries of 62–108% were obtained. Linearity (r 2 ) above 0.96 was achieved for all compounds using concentrations in the range 0.25–2.0 × MRL. Intraday precision with coefficients of variation (n = 6) lower than 15.0% and inter-day precision lower than 17.3% were obtained for three concentration levels in the range 0.5–1.5 × MRL. Accuracy was 87–108%. Limits of detection and quantitation, as well as decision limit, detection capability, robustness and applicability, were evaluated using >600 real milk samples.